GROWTH AND YIELD OF OKRA (Abelmoschus esculentus L. Moench) AS INFLUENCED BY FERTILIZER APPLICATION UNDER DIFFERENT CROPPING SYSTEMS - Aderemi Isaiah Makinde; Kehinde O Oyekale; David S Daramola (Socio-Economics/Agribusiness Department, 2022)
Reduction in agricultural land with increasing population has led to a need to combined more than one crop to maximize limited land resources and thus require an improvement. A field experiment was conducted during the growing seasons of 2019 in two locations in Southwest Nigeria to assess the effect of cropping system and fertilizer application on the yield of okra intercropped with jatropha. The experiment was a split-plot arrangement in a Randomized Complete Block design, replicated three times. Fertilizer types were the main plots (NPK, Organic, Organic + NPK (50:50) and control while the cropping systems (sole okra, sole Jatropha and their intercrop) was sub-plot. Data were collected to determine okra growthÂ includes: plant height, number of leaves/ plant, leaf area and the yield by number of days to 50 % flowering, number of fruits/ ha, fruit yield and fruiting duration. Jatropha growth parametersÂ taken include:Â plant height (cm), number of leaves/plant. Results showed that okra can be intercropped with jatropha without any reduction it its performance. Growth of jatropha as well as okra yield was significantly better in fertilized plots than the unfertilized plots, with complementary use of organic and inorganic fertilizer producing the best results.